Target independence of the ‘proton spin’ effect - Graham Shore (Nuclear Physics B - Proceedings Supplements, 1994)
Recent work by the author in collaboration with S. Narison and G. Veneziano on the EMC-SMC-SLAC `proton spin' effect is reviewed. This uses a novel approach to deep inelastic scattering in which the matrix elements arising from the OPE are factorised into composite operator propagators and proper vertices. For polarised $μ p$ scattering, the composite operator propagator is equated to the square root of the first moment of the QCD topological susceptibility, $\sqrt{χ~′(0)}$. We evaluate $χ~′(0)$ using QCD spectral sum rules and find a significant suppression relative to its OZI expectation. This is identified as the source of the violation of the Ellis-Jaffe sum rule for the first moment of the polarised proton structure function $g_1~p$. Our predictions, $\int_0~1 dx g_1~p(x;Q~2=10GeV~2) = 0.143± 0.005$ and $ΔΣ =0.353± 0.052$, are in excellent agreement with the new SMC data. This supports our earlier conjecture that the suppression in the flavour singlet component of the first moment of $g_1~p$ is a target-independent feature of QCD related to the $U(1)$ anomaly and is not a special property of the proton